The linguistics of olfaction - Jedrzejowski, Lukasz; Staniewski, Przemyslaw (Typological studies in language,, 2021)
"This volume presents novel cross-linguistic insights into how olfactory experiences are expressed in typologically (un-)related languages both from a synchronic and from a diachronic perspective. It contains a general introduction to the topic and fourteen chapters based on philological investigation and thorough fieldwork data from Basque, Beja, Fon, Formosan languages, Hebrew, Indo-European languages, Japanese, Kartvelian languages, Purepecha, and languages of northern Vanuatu. Topics discussed in the individual chapters involve, inter alia, lexical olfactory repertoires and naming strategies, non-literal meanings of olfactory expressions and their semantic change, reduplication, colexification, mimetics, and language contact. The findings provide the reader with a range of fascinating facts about perception description, contribute to a deeper understanding of how olfaction as an understudied sense is encoded linguistically, and offer new theoretical perspectives on how some parts of our cognitive system are verbalized cross-culturally. This volume is highly relevant to lexical typologists, historical linguists, grammarians, and anthropologists"--